Pendidikan Intregrasi Di Pondok Pesantren Ulil Albab, Nganjuk - Wasito Wasito; Makhfud Makhfud (Universitas Islam Tribakti Lirboyo Kediri, 2020)
The development of the implementation of education in Indonesia towards the concept of integration in all fields of science. This practice was also carried out at the Ulil Albab Islamic Boarding School, Ngronggot Nganjuk. This study uses a qualitative method by interviewing all stakeholders in the Ulil Albab Islamic Boarding School. The results of this study indicate. First, integrated infrastructure. Second. Institutional integrity. Third, curriculum integration. Fourth, management integration. Fifth, the integration of traditions. While the target to be achieved is,